Jordan : Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report, 2005)
The staff report for the Post-Program Monitoring Discussions on Jordan focuses on economic developments and policies. The macroeconomic policy mix included prudent budgetary management and a credit policy supportive of economic expansion. Monetary developments reflected the brisk growth in credit to the private sector on account of the buoyant economic activity and government domestic financing needs related to delays in privatization. Reflecting buoyant tax revenues and tight expenditure management, the fiscal position has strengthened, and the total public debt/GDP ratio has fallen.